Pengaruh harga minyak, inflasi, suku bunga, dan kurs terhadap indeks saham sektoral IDXEnergy - Novianto, Fajar; Paramita, R.A. Sista (Jurnal Ilmu Manajemen, 2023)
Since 2020, energy commodity prices have shown recovery after falling due to the impact of COVID-19. However, during this recovery period, the Russia-Ukraine war occurred. Russia was sanctioned by an energy embargo which further pushed the price of energy commodities, including oil. On the other hand, the events of the Russian-Ukrainian war also caused turmoil in macroeconomic factors such as inflation, interest rates, and exchange rates. This study examines the effect of oil prices and macroeconomic factors on the energy sector stock index. The independent variables used in this study are oil prices and macroeconomic factors such as inflation, interest rates, and exchange rates. The period used in this study is the period from 2020 to 2022. The sampling technique used is a saturated sample where the entire population will be sampled. The data analysis technique used is multiple linear regression. The results showed that partial oil prices and exchange rates had no significant effect. In contrast, the inflation variable had a significant positive effect, and interest rates had a significant negative effect. An increase in inflation will reduce the value of wealth, so investors should invest in stocks in the energy sector when there is an increase in inflation. Conversely, an increase in interest rates makes investment alternatives in deposits more attractive with a lower level of risk than stocks.